Analyzing the potential chemical substances reducing the ambient carbon dioxide from Sansevieria sp. - Rahardian Wicaksono, Rizky; Setyo Leksono, Amin; Warih Marhendra, Agung Pramana; Damanhuri (Jurnal Pembangunan dan Alam Lestari, 2024)
Air pollution is a global problem faced by most large cities worldwide. Air has a very important role in the lives of humans and other living creatures. Air is a natural resource whose sustainability must be protected into the future. Therefore, efforts are needed to contain CO levels in the air using Sansevieria plants. Therefore, this research aims to obtain optimal levels of CO-absorbing compounds in Sansevieria sp. as carbon monoxide gas reducers. This type of research uses experimental methods (quasi-experimental). Quantitative data collection was carried out based on the results of experiments in the field. Field experiments with a Complete Random Design (Complete Random Design) with the conditions of each experiment assumed to be homogeneous. The research results show this plant contains Aliphatic Hydrocarbons and Primary Aliphatic Alcohols compounds. Keywords: air pollution, CO gas, sansevieria